Revisionism and the dangers of deliberate lies from Hannah Arendt's perspective - dos Passos, Fábio Abreu (2022)
The production of false news, nowadays called Fake News, which aims to disseminate improbable information, should not be understood as a recent political phenomenon. Lying as a way to hide sensitive data is a tradition as for political game; what is new is the deliberate attempt to misrepresent reality, an effective contemporary practice for the purposes of those who intend to shape the world to suit “their wishes”. Our bet is that revisionism must be understood as a movement to promote and disseminate deliberate lies, which have the purpose of adulterating the world, denying, for example, the existence of historical facts such as the Holocaust and the Brazilian Military Civil Dictatorship. An antidote capable of mitigating the effects of deliberate lying is factual truth, which ensures that the world is not threatened in its constitutive structures, namely, that the actions that occur in it are not altered and the memories of those actions are not corrupted.